Beyond Coding Blocks: Unveiling Elementary Teachers’ Navigation of LOTS and HOTS in Computational Thinking Classrooms - Rafika Putri; Muhammad Rusli; Julien Chintya; Halani Felda Sunbanu; Alse Ona Sabat; Dyen Erni Lakapu; Nurul Mahruzah Yulia (MIMBAR PGSD Undiksha, 2026)
Integrating computational thinking in elementary education requires teachers to design programming-based learning that promotes HOTS, although its implementation still faces various challenges.This study aims to analyze elementary school teachers’ understanding and perceptions of HOTS and Lower-Order Thinking Skills (LOTS) within programming-based learning contexts. This study employed a qualitative approach involving 40 elementary school teachers selected purposively. Data were collected through a Likert-scale questionnaire and semi-structured in-depth interviews as the primary instruments. Data analysis was conducted using a six-phase thematic analysis to identify patterns and meanings emerging from the data. The findings reveal that teachers demonstrate a high level of conceptual understanding of HOTS/LOTS and strong competence in designing HOTS-oriented assessments. Nevertheless, moderate challenges persist, particularly related to time constraints, student readiness, and resource limitations. On the other hand, systemic support is perceived to be very high and serves as a key enabling factor in strengthening teachers’ readiness. This study concludes that integrating HOTS into programming learning requires a supportive educational ecosystem, strengthened by continuous professional development, authentic assessment, and professional learning communities.